2009
DOI: 10.2140/jomms.2009.4.1341
|View full text |Cite
|
Sign up to set email alerts
|

The elusive and fickle viscoelastic Poisson’s ratio and its relation to the elastic-viscoelastic correspondence principle

Abstract: The conditions for the applicability of the elastic-viscoelastic correspondence principle (analogy) in the presence of any of the five distinct classes of viscoelastic Poisson's ratios (PR) are investigated in detail. It is shown that if Poisson's ratios are time-dependent, no analogy in terms of PRs is possible, except for two of the classes under specifically prescribed highly limited conditions. Separately, the severely restrictive conditions involving time-independent PRs are discussed in detail. Failure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…(10) or (2a), respectively. Of those two equations, the former involves a convolution, whereas the latter does not, which shows that the correspondence principle is not applicable to the creep Poisson's ratio ν c , as already noted by Hilton (2001Hilton ( , 2009Hilton ( , 2011 and Tschoegl et al (2002). Note that Lakes and Wineman (2006) found a relationship between the two Poisson's ratios ν r and ν c that differs from that given in Eq.…”
Section: The Elastic-viscoelastic Correspondence Principlementioning
confidence: 89%
“…(10) or (2a), respectively. Of those two equations, the former involves a convolution, whereas the latter does not, which shows that the correspondence principle is not applicable to the creep Poisson's ratio ν c , as already noted by Hilton (2001Hilton ( , 2009Hilton ( , 2011 and Tschoegl et al (2002). Note that Lakes and Wineman (2006) found a relationship between the two Poisson's ratios ν r and ν c that differs from that given in Eq.…”
Section: The Elastic-viscoelastic Correspondence Principlementioning
confidence: 89%
“…Since the correspondence principle has been proven inapplicable when PRs are involved [87] [88] [89], the usual elastic relations for shear and bulk moduli have no viscoelastic counterparts in terms of PRs, i.e. , , 1 2 2 1…”
Section: ( ) ( )mentioning
confidence: 99%
“…None of the five PR categories defined in [87] [88] [89] fit these needed real time prescriptions, nor does the sixth class fit the constraints imposed by (32). Consequently, it would appear that no universal EVCP based on PRs can be rationally deduced or justified.…”
Section: T VI Jj X T X T T X T T X Jmentioning
confidence: 99%
“…The impossibility of formulating an elastic-viscoelastic correspondence principle (analogy) (EVCP) [10,11] based on PRs has been proven by different analytical formulations in [12][13][14]. Yet, publications continue to appear in respectable archival journals which miss the point by either assuming that viscoelastic PRs are constants or that the EVCP applies to PRs or by extending special PR concepts into general regions where they have been proven to be inapplicable or by using all of the above.…”
Section: Introductionmentioning
confidence: 99%
“…The Class III PR definition [12][13][14] as the ratio of two transforms of perpendicular strains has no physical denotation and is less than useful in its time-space inversion counterpart. Furthermore, it can be shown that PRs cannot be part of viscoelastic constitutive relations and that they cannot encompass the EVCP.…”
Section: Introductionmentioning
confidence: 99%